Efektivitas Media Video Tutorial Dalam Meningkatkan Keterampilan Vokasional Membuat Es Kelapa Muda Bagi Anak Tunarungu - Fitri, Fauziatul; Fatmawati, Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2021)
This research was motivated by the problems found in SLB 1 Painan, there were five deaf grade VII students who had been directed to learning skills. The skills at school have not been maximized because there is no special teacher for skills skills at school, there is no making drinks, usually only making food. Then when learning the teacher prioritizes the lecture method and the division of tasks is different for each student.This study used a type of pre-experiment research, one group pretest and posttest design. The aim is to prove that the video tutorial media is effective in improving the skills of making young coconut ice. The sampling technique of this research is saturated sampling technique. The data collection technique is an action test that is carried out during the pretest to determine the student's aeal ability in making coconut ice, then given a treatment with a video tutorial, and then given a posttest.The data collection tool was in the form of a research instrument developed based on the analysis task. The pretest and posttest results were processed and compared with the Wilcoxon Sign Rank Test. Namely research data obtained on average at the pretest is 59.20 while for the posttest is 85,00. The data that was processed more scientifically using the Wilcoxon test obtained the rank tast value between the pretest and posttest -2,023 with Asymp. Sign (2 tailed) 0,043. The predetermined reward a. = 0.05. The alternative hypothesis is accepted because the probability <of the predetermined probability is 0,043 <0.05. It can be concluded that it is proven that the use of video tutorial media is effective in improving vocational skills in making young coconut ice in class VII deaf children at SLB 1 Painan.